Open Educational Practices in Australia: A First-phase National Audit of Higher Education - Stagg, Adrian; Nguyen, Linh; Bossu, Carina; Partridge, Helen; Funk, Johanna; Judith, Kate (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
For fifteen years, Australian Higher Education has engaged with the openness agenda primarily through the lens of open-access research. Open educational practice (OEP), by contrast, has not been explicitly supported by federal government initiatives, funding, or policy. This has led to an environment that is disconnected, with isolated examples of good practice that have not been transferred beyond local contexts.This paper represents first-phase research in identifying the current state of OEP in Australian Higher Education. A structured desktop audit of all Australian universities was conducted, based on a range of indicators and criteria established by a review of the literature. The audit collected evidence of engagement with OEP using publicly accessible information via institutional websites. The criteria investigated were strategies and policies, open educational resources (OER), infrastructure tools/platforms, professional development and support, collaboration/partnerships, and funding.Initial findings suggest that the experience of OEP across the sector is diverse, but the underlying infrastructure to support the creation, (re)use, and dissemination of resources is present. Many Australian universities have experimented with, and continue to refine, massive open online course (MOOC) offerings, and there is increasing evidence that institutions now employ specialist positions to support OEP, and MOOCs. Professional development and staff initiatives require further work to build staff capacity sector-wide.This paper provides a contemporary view of sector-wide OEP engagement in Australia—a macro-view that is not well-represented in open research to date. It identifies core areas of capacity that could be further leveraged by a national OEP initiative or by national policy on OEP.